2004
DOI: 10.1002/clc.4960270311
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram and clinical characteristics of patients referred for cardiac transplantation: Implications for pacing in heart failure

Abstract: SummaryBackground: Permanent pacing for the treatment of heart failure (HF) has been the subject of intense research over the past decade. Those with conduction abnormalities may benefit most from pacing. The incidence of these conduction abnormalities in patients referred for cardiac transplantation and its relationship to outcome has not been well described.Hypothesis: This study sought to determine the incidence of these abnormalities and to correlate these findings to outcome in this patient population.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Prolongation of QRS (Ն120 ms) is a significant predictor of LV systolic dysfunction in patients with HF (4,8,10,11,22). In contrast, the significance of QRS prolongation has not yet been evaluated in HF with a normal LVEF and diastolic dysfunction.…”
Section: Function and Clinical Statusmentioning
confidence: 88%
See 2 more Smart Citations
“…Prolongation of QRS (Ն120 ms) is a significant predictor of LV systolic dysfunction in patients with HF (4,8,10,11,22). In contrast, the significance of QRS prolongation has not yet been evaluated in HF with a normal LVEF and diastolic dysfunction.…”
Section: Function and Clinical Statusmentioning
confidence: 88%
“…In contrast, the significance of QRS prolongation has not yet been evaluated in HF with a normal LVEF and diastolic dysfunction. In patients with HF, an inverse correlation exists between QRS prolongation and LVEF (Table 1) (4,8,10,11,13,18). In a study of nearly 3,500 patients with HF, Shenkman et al (7) found a stepwise increase in the prevalence of systolic LV dysfunction as QRS complex duration increased progressively above 120 ms. A more recent study conducted in 343 patients with HF reported LVEF of 41%, 36%, 29%, and 25% in patients with QRS durations of Ͻ100 ms, 100 to 119 ms, 120 to 149 ms, and Ն150 ms, respectively (10).…”
Section: Function and Clinical Statusmentioning
confidence: 94%
See 1 more Smart Citation
“…It is particularly important since some studies showed QRS duration increases as left ventricular function worsens (Iuliano et al, 2002;Stellbrink et al, 1999). Others (Freudenberger, Sikora, Fisher, Wilson, & Gold, 2004;Shamim et al, 1999;Silverman, 1995), demonstrated that patients with QRS prolongation have higher all-cause mortality and possibly a higher incidence of sudden death (or cardiac death) than those with narrow QRS complexes. On the other hand, PR interval duration did not differ between high and moderate exercise(HVE = 116.6 ± 24.5 ms vs. MVE = 134.1 ± 26.1 ms), but the HVE group showed lower limits of PR compared to recommended standard values(between 120 ms -200 ms).…”
Section: Discussionmentioning
confidence: 99%
“…HF is the leading indication for hospitalization in elderly patients (SOLVD Investigators 1991 ;Packer et al 1996 ;MERIT Merit -HF Study Group 1999 ;Bubien and Ching 2004 ;American Heart Association 2008 ), accounting for $40 billion annual expenditures in the United States (O ' Connell and Bristow 1994 ;McMurray and Stewart 2000 ). and a LVEF < 35% secondary to ischemic and nonischemic cardiomyopathy (Huang et al 1995 ;Silverman et al 1995 ;Shamin et al 1998 ;Juliano et al 2002 ;Shenkman et al 2002 ;Bade et al 2004 ;Freudenberger et al 2004 ). These electrical timing abnormalities adversely effect critical mechanical interactions that further impair LV function.…”
mentioning
confidence: 99%